The Japanese Tax Reform : Efficiency Versus Equity. (IMF Working Papers; Working Paper ;, 1990)
Efficiency, equity (fairness), and simplicity are three key words in characterizing the principles of proposed tax reforms in many countries. The internationalization of the financial market through capital mobility among the industrial countries is a recent phenomenon and it is possible that the effect of domestic tax reform is dictated by international capital flows. The purpose of this paper is to examine whether the tax reform proposed recently in Japan satisfies the above principles, in particular, efficiency and equity, and to investigate the effects not only on the real economy in Japan, but also on capital outflows from Japan to abroad. Also, the aging problem is examined briefly.